Positive feedback: a tool for quality education in field of medicine - Mandhane, Nisha; Ansari, Sharique; Shaikh, Tanveer Parvez; Deolekar, Sandesh (International Journal of Research in Medical Sciences, 2017)
Background: Feedback in medical education is an integral and important constituent of teaching as it encourages and enhances the learners' knowledge, skills and professional performance. Feedback has to be delivered in an appropriate setting; it should focus on the performance and not on the individual; should be clear and specific; delivered in non-judgmental language; should emphasize positive aspects; be descriptive rather than evaluative; and should suggest measures for improvement. Methods:20 Post Graduate Student from surgery department was selected for the study. Results:Constructive feedback is defined as the act of giving information to a trainee through the description of his/her performance in the observed situation. It emphasizes the strengths of the session and areas which require improvement. The processes of giving and receiving feedback are skills that can be acquired only with practice with improvement in Pg student’s skill and knowledge. Conclusion: To integrate the concept of feedback in medical education, training of the trainers pertaining to techniques of adult learning and how to give feedback to trainees are foremost requirements. Interactive feedback is indispensable in bringing about professional development and overall improvement in doctors.